In Silico Study of Secondary Metabolite in Asiatic Pennywort (Centella asiatica) as a Drug Compound for Blood Cancer (Acute Lymphoblastic Leukemia (ALL)) Targeting JAK-2 Receptor - Anjelina, Martina; Renaldi, Fahri; Shabira, Kalya Kama; Febriyanti, Selly Trianingrum; Wulandari, Rizky Prasiska; Nurdin, Halwa Aulia; Nuwarda, Rina Fajri (Indonesian Journal of Chemical Science, 2025)
Acute Lymphoblastic Leukemia (ALL) is a type of cancer with clinical manifestations such as fever, pallor, bleeding, children appear lethargic, bone and joint pain, enlarged liver, spleen, and enlarged lymph. One of the causes of ALL is due to mutations in the JAK-2 receptor. The purpose of this In Silico study is to find new candidate compounds as ALL therapy in Asiatic Pennywort (Centella asiatica) plant by Lipinski’s RO5 analysis, ADME-Tox, pharmacophore modelling, and molecular docking. The results showed that luteolin can be declared as a lead compound in Asiatic Pennywort plant that has potential in the treatment of acute lymphoblastic leukemia due to its interaction with JAK-2 receptor with an inhibition constant of 0.23736 uM and binding energy of -9.04 kcal/mol. In addition, the predictions of Lipinski's RO5 and ADME-Tox luteolin also meet the requirements to be made into oral preparations and further research can be carried out.